Study of Supply Change Industry Management in Indonesian Companies - Bayu Nur Kuncoro; Roisita Cindrakasih; Sidik (MultiTech Publisher, 2023)
Implementation of supply chain management is not as easy as imagined. Company must have a good and reliable management information system and workforce who are skilled and experienced in supply chain management. Socio-economic changes like this produce obstacles and challenges that must be faced. This requires every company to develop a business strategy in order to compete with other companies. In this cycle or chain there are several organizations that work in different scopes but have the same goal, namely to procure goods and distribute them to the final consumers effectively and efficiently. Supply Chain Management is very important to do to expedite the production process and marketing process to meet consumer needs. In order for supply chain control to be effective, it is necessary to have a smooth flow of information and mutual trust between parts, be it suppliers, companies or consumers.